Laying open (deroofing) and curettage of sinus as treatment of pilonidal disease: a systematic review and meta‐analysis. Issue 1 (27th November 2015) - Garg, Pankaj; Menon, Geetha R.; Gupta, Vikas
Abstract: Background: Laying open (deroofing, not excision) and curettage of the sinus is a minimally invasive procedure to treat pilonidal disease. A consensus on its efficacy and outcomes has not been reached. We reviewed and meta‐analysed the efficacy of this procedure. Methods: PubMed, Medline, Scopus, Ovid, Cochrane central register of controlled trials (CENTRAL) and Google scholar databases were searched. All studies describing laying open (not excision) of sinus with curettage of the tract to treat pilonidal disease (simple and complicated) were included. The primary outcome parameter was recurrence and the secondary outcome parameters were complication rate, operating time, return to work and healing time. Results: A total of 1194 studies were screened. Out of these, 13 studies were finally included for the analysis. The analysis ( n = 1445) demonstrated a net proportion meta‐analysis (random effect) pooled rate of 4.47% (95% CI = 0.029–0.063) for recurrence, 1.44% (95% CI = 0.005–0.028) for complications, 34.59 min (95% CI = 13.58–55.61) for operating time, 21–72 days for healing time and 8.4 days (95% CI = 5.23–11.72) for return to work. The procedure was possible under local anaesthesia in seven out of 13 studies. Conclusions: The meta‐analysis demonstrates that laying open (deroofing) and curettage has distinct advantages. These are high success rate, possible in all types of pilonidal disease (simple and complex), low complication rate, short operating time and early return to normal routine and work. This procedure can be conveniently under local anaesthesia as an outpatient procedure.